Mild cold stress specifically disturbs clustering movement of DFCs and sequential organ left-right patterning in zebrafish - Liu, Min; Zou, Xinyu; Fu, Mao; Bai, Xinping; Zhao, Yongyan; Chen, Xin; Wang, Xiaoyu; Wang, Peijian; Huang, Sizhou (Frontiers in Cell and Developmental Biology, 2022)
In poikilothermal animal, the distinct acclimatization ability of different organs had been addressed, while the tissue specific role of cold stress in early development is largely unknown. Here we discovered that, besides the role in delaying embryonic development, mild cold stress (22°C) does not disturb the multiple-organ progenitor specification, but gives rise to organ left-right (LR) patterning defect. In mechanism, the data showed that mild cold stress down-regulates the expression of cell-adhesion genes cdh1 and cdh2 during gastrulation, especially in dorsal forerunner cells (DFCs), which partially disturbing the clustering movement of DFCs, Kupffer's vesicle (KV) morphogenesis and ciliogenesis. As the result, the defect of KV/cilia disrupts the asymmetric Nodal signaling and the subsequent heart and liver LR patterning. In conclusion, our data first identified that, in early development, the DFCs is more sensitive to mild cold stress, and mild cold stress represses the expression of cell-adhesion related gene cdh1 and cdh2. This role partially disturbs the clustering movement of DFCs, which resulting in defective KV/cilia development and the sequential organ LR patterning defect.